West Sumatra Education is the Leading Sector in Facing the Covid-19 Pandemic - Arrazy, Masruqi (Universitas Muhammadiyah Sorong, 2021)
The economy of West Sumatra experienced an economic contraction in 2020 due to the Covid-19 pandemic. However, the education sector experienced better growth compared to national growth. Seeing this, the potential of this sector in West Sumatra needs to be analyzed so that it can be seen whether this sector can be chosen as a priority sector in spurring West Sumatra's economic growth to enter the new normal period. The analysis in this study uses secondary data with the classic Shift Share method. The data in this study are Indonesia's Gross Domestic Product according to Constant Prices and the Gross Regional Domestic Product of West Sumatra according to Constant Prices with the 2019 and 2020 data periods. From the analysis results, it is known that the education sector is growing progressively. This sector in West Sumatra is growing faster than the national one and its competitiveness is better than other sectors in West Sumatra. Another thing according to this research is that the education sector can affect several other sectors during the pandemic. So that this sector is very worthy of being the leading sector in dealing with the new normal situation.